The efficiency of the tax examiner and its impact on discovering the artificial adjustment of profits: Applied research in the General Tax Authority (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The aim of the research is to measure the length between the variable the efficiency of the tax examiner with its dimensions represented by (scientific questions, practical process (experience), training and development, impartiality and independence, ethics of the profession) and the approved variable discovering the artificial adaptation of profits, and the degree of arrangement of those dimensions its importance and priority, and the research problem has been identified  In a main question that is there any effect of copying the images of the image examiner in discovering the adaptation, the financial statements and reports of the companies (X, Y) and the banks (A, B) were relied on in the interpretation of the results, the facilities of the personal interviews in them, and the data was analyzed by relying on the statistical program (  SPSS V.18) and (AMOS V.24) coefficient coefficient of variation, coefficient coefficient, coefficient coefficient, coefficient, coefficient, and among the most prominent results it reached was showing that there is an innovative coefficient that has a significant effect on the dimensions of the tax examiner’s efficiency collectively or individually in discovering localization  This indicates the extent of the great positive impact that achieves great success in discovering the artificial profits.